Jigsaw-Type Cooperative Learning in Improving Basic Electrical Learning Outcomes of Students of SMKN 2 Bitung - Maasje Elungan; Eklesiano Lamo; Fransiskus Seke; Billy Kilis; Nontje Sangi (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2024)
This research is classroom action research that aims to improve the learning process by applying the jigsaw-type cooperative learning model to improve Basic Electrical learning outcomes for Class X TITL students at SMK Negeri 2 Bitung, carried out in March 2021. Techniques and data collection tools in this research used descriptive statistical analysis of the data in student test results from documents and a list of scores. This study uses two stages of the cycle where the first cycle consists of IV meetings and the second cycle consists of IV meetings. Cycle I students achieve 55% incomplete and 45% complete learning outcomes. Cycle II students achieve 0% incomplete and 100% complete learning outcomes. The increase in learning outcomes was seen in the second cycle, namely the results of student learning achievement of 100% complete from the number of 20 students. Thus, learning using the jigsaw-type cooperative learning model can improve the learning outcomes of class X TITL students at SMK Negeri 2 Bitung.